Dual-signaling electrochemical ratiometric strategy for simultaneous quantification of anticancer drugs - Hatamluyi, Behnaz; Sadeghian, Reihaneh; Sany, Seyedeh Belin Tavakoly; Alipourfard, Iraj; Rezayi, Majid (Talanta (Oxford), 2021)
A novel and unique ratiometric electrochemical sensing strategy for highly reliable and selective simultaneous quantification of Irinotecan (IRI) and 5-Fluorouracil (5-FU) has been developed based on Pd–Au/MWCNT-rGO nanocomposite. Introduction of Pd–Au/MWCNT-rGO significantly improved the speed of electron transport, specific surface area, and electrical catalytic ability of sensing system due to synergistic effect of Pd–Au bimetallic nanoparticles and MWCNT-rGO hybrid structure. The assay strategy was based on the use of ferrocene (Fc) as reference electroactive substance and IRI and 5-FU as analytes with three oxidation peaks at different potentials (Fc at +0.20 V, IRI at +0.58 V, and 5-FU at +1.17 V). The oxidation peak currents of the IRI and 5-FU were gradually enhanced while that of Fc remained almost constant with continuous adding of IRI and 5-FU. By using IIRI/IFc and I5-FU/IFc signals as output, the designed ratiometric system showed good performance with a wide linear range of 0.05–40 μM for IRI and 0.05–75 μM for 5-FU and low detection limit of 0.0061 μM and 0.0094 μM for IRI and 5-FU, respectively. This study proved that ratiometric strategy is able to eliminate disturbance caused by the sensing environment and possess high sensitivity, reproducibility, stability, and selectivity toward anticancer drugs detection, over potential interferents as well as opens a new procedure for reliable and selective simultaneous analysis of other analytes. •A dual-ratiometric electrochemical strategy was developed to simultaneously detect anticancer drugs for the first time.•The combination of thePd–Au/MWCNT-rGO and ratiometric strategy greatly improved analytical performance of the sensor.•The proposed strategy has accurately determined anticancer drugs in real samples without any matrix effect.